A Critical discussion of the impact of the right to fair value, good quality and safety in terms of the Consumer Protection Act 68 of 2008 on the Agricultural Industry in South Africa - Barnard, Jacolien (University of Pretoria, 2014)
Dissertation (LLM)--University of Pretoria, 2013.